Analysis of Field Characteristics for Irrigation System Design: A Case Study - Uche, U. E.; Soretire, L. K.; Omiogbemi, I. M. B.; Iwuoha, L. I.; Aserifa, W. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The determination of field characteristics is key to the successful installation of irrigation because the water use efficiency depends on the soil infiltration rate, storage capacity, permeability, and plasticity. The shear strength of the soil was also determined for the purpose of construction of water abstraction systems. The applicability of irrigation for paddy rice cultivation in the Igwu River Basin was assessed as a case study using secondary data from the Igwu River World Bank Rice Project and Abia State Ministry of Agriculture. Primary data was generated by field and laboratory soil tests. The soil survey and project land classification were based on the United State Bureau of Reclamation general land classification standard on limiting factors to irrigation. Field and laboratory tests were used to generate data on the specific gravity of soil particles and the compaction characteristics to determine the dry, moist, saturated, and buoyant unit weight of the soil. Consistency limits, plasticity, shear, and compressive parameters as well as coefficient of permeability, infiltration characteristics and soil storage capacity were also determined. The result showed that the soil profile is well drained to a depth of about 1m and of characteristic agricultural nature, rich in mineral nutrient and having a pH of 6.7. The soil is of good workability, with largely fine to medium texture, characterized by dull orange. (7.5yrs 6/4 dry, brownish black (10yrs 3/2) wet topsoil. The topsoil is made up of sandy loam of weak angular structure, few fibrous roots and, of mixed humous, with few fine and continuous pores. It was further, observed that erosion was minimal because of forest cover and the area holds a high potential for irrigated agriculture. It is therefore the opinion of the authors that the study site is suitable for paddy rice irrigation.